Application of Ecological Architecture Concepts to Industrial Villages in Surabaya (Case Study: Gundih Village) - Dian Pramita Eka Laksmiyanti; Esty Poedjioetami (OPSI, 2021)
Global warming encourage people to care more about energy consumption. Metropolitan city like Surabaya has a complex problem in it such as high density, fast growth and development, high energy consumption, and many more. Ecological city supposed to encourage smart citizen, environmentally friendly and humane. It obviously not easy, requires good cooperation between the government, sector managers and the community. The Surabaya mayor's approach and the socialization of the importance of implementing green architecture in each area have succeeded in raising public awareness to create a harmonious, ecological and energy-conscious environment. Apart from the ecological aspects, what makes Surabaya the most advanced city in Indonesia is economic growth. The fast economic growth cannot be separated from the motivation of the Mayor of Surabaya in growing small and medium industries. Kampung Gundih is one of the kampong that has successfully implemented the ecological concept and has become the most advanced home industry in Surabaya by winning the Surabaya Green and Clean in recent years. This study aims to identify and describe the application of Green architecture and ecological concepts in small industrial-based settlements in Kampung Gundih, Surabaya. The method used in this research is descriptive qualitative. The results obtained are a review of the implementation of the concept of ecological architecture in rural areas and small industries, a description of the integrated water management process, and environmental management strategies in Kampung Gundih Surabaya.